346 Cancer-associated Fibroblasts in Glioblastoma Mouse Model Impact the Lymphoid Cells in the Tumor Microenvironment. (1st March 2022) - Kim, Timothy Y.; Srivastava, Siddhartha; Patel, Kisha K.; Pant, Ayush; Lim, Michael
Abstract : INTRODUCTION: Cancer-associated fibroblasts (CAFs) have been demonstrated to play a prominent role in various solid tumors by remodeling and reprogramming the tumor microenvironment. Recently, they have been identified in glioblastoma (GBM) patients and believed to have a protumoral effect in GBM progression. Not only have CAFs been found to affect the myeloid compartment, but also the lymphoid compartment. Studies have shown that CAFs may mediate dysfunction of CD8 T-cells, decrease their cytotoxicity, and induce apoptosis. METHODS: 6-week C57BL/6J wild-type female mice were intracranially implanted with either Gl261-luciferase (Gl261-luc) tagged cells alone or in combination with NIH/3T3 embryonic fibroblasts. Mice were monitored for survival in 4 arms (Gl261 vs Gl261 + anti-PD-1 vs Gl261 + NIH3T3 vs Gl261 + NIH3T3 + anti-PD-1) or sacrificed on post-implantation day 18 for flow cytometry analysis. Anti-PD-1 treatments occurred on post-implantation D10, 12, and 14. For flow cytometry, immune cells were isolated, were plated in a 96-well plate, and stained with antibodies for CD45, CD3, CD8, PD1, TIM3, LAG3, IFN-gamma, and TNF-alpha. RESULTS: The fibroblast-glioblastoma arms had significantly worse survival than non-fibroblast arms. Anti-PD-1 significantly improved survival in the fibroblast-glioblastoma arm. Fibroblast arms had statistically significant increased Cd8+ T-cell infiltration, reduced TIM-3 expression, reduced LAG3 expression, reduced IFN-gamma production in CD8+ T-cells, and trended toward significantly increased PD-1 expression. CONCLUSION: The addition of fibroblasts led to greater CD8+ T-cell infiltration but resulted in worse survival and an overall exhausted T-cell phenotype, as evidenced by equal or increased expression of LAG3 and PD-1. This corroborates why anti-PD-1 administration resulted in greater survival. Interestingly, TIM-3 expression was decreased in the fibroblast arms.